Effect of time delay in inter-hospital transfer on outcomes of endovascular treatment of acute ischemic stroke - Pardo, Keshet; Naftali, Jonathan; Barnea, Rani; Findler, Michael; Perlow, Alain; Brauner, Ran; Auriel, Eitan; Raphaeli, Guy (Frontiers in Neurology, 2023)
Background: Endovascular treatment (EVT) with mechanical thrombectomy is the standardof-care for large vessel occlusion (LVO) acute ischemic stroke (AIS). The most common approach these days is performing EVT in comprehensive stroke center (CSC) and transferring relevant patients for EVT from primary stork center (PSC). Rapid and efficient treatment for LVO is a key factor to achieve good clinical outcome.We present our retrospective cohort of patients who underwent EVT between 2018-2021, including direct admissions and transferred patients from PSC. Primary endpoints were time intervals (door-to-puncture, onset-to-puncture, door-to-door), and favorable outcome (mRS ≤2) after 90 days. Secondary outcomes were successful recanalization, mortality rate, and symptomatic intracranial hemorrhage (sICH). Additional analysis was performed for transferred patients not treated by EVT; endpoints were time intervals, favorable outcome, and reason for excluding EVT.Results: Between a total of 405 patients, 272 were admitted directly to our EVT center and 133 were transferred, there was no significant difference between groups in the occluded vascular territory, baseline NIHSS, wake-up strokes and thrombolysis rate. Patients admitted directly had shorter door-to-puncture time than transferred patients (190 minutes versus 293 minutes, p<0.001). Door-to-door shift median time was 204 minutes. We found no significant difference in functional independence, successful recanalization rates, or sICH rate. The most common reason for transferred patients to be excluded from EVT was clinical or angiographic improvement (55.6% patients).Our results show that transferring patients to EVT center does not impair clinical outcomes, despite the expected delay in EVT. Reassessment of patients upon arrival at the CSC is crucial, and patient selection should be done relaying both on time and tissue window.